Scientific objectives and payloads of the lunar sample return mission—Chang'E-5. Issue 1 (1st January 2022) - Zhou, Changyi; Jia, Yingzhuo; Liu, Jianzhong; Li, Huijun; Fan, Yu; Zhang, Zhanlan; Liu, Yang; Jiang, Yuanyuan; Zhou, Bin; He, Zhiping; Yang, Jianfeng; Hu, Yongfu; et al.
Abstract: In the early morning on December 17, 2020 Beijing time, China's chang'E-5 probe successfully returned to the Earth with 1731 g of lunar samples after completing drilling, shoveling, packaging of lunar soil and scientific exploration on lunar surface. It is the successful completion of the third phase of China's lunar exploration project, namely "circling, landing and returning to the moon". The scientific objectives of CE-5 mission are to carry out in situ investigation and analysis of the lunar landing region, laboratory research and analysis of lunar return samples. This paper analyzes scientific exploration tasks of CE-5 mission conducted on the lunar surface, and carries out the scientific payload system architecture design and individual scientific payload design with the scientific exploration task requirements as the target, and proposes the working mode and main technical index requirements of the scientific payloads. Based on the preliminary geological background study of the Mons Ruemker region which is the landing region of CE-5, the lunar scientific exploration and the laboratory physicochemical characterization of the return samples are of great scientific significance for our in-depth understanding of the formation and evolution of the Earth-Moon system and the chemical evolution history of the lunar surface.